Concept of Pedagogy and Andragogy Education - Kathryn Holmes; Greg Preston (HM Publisher, 2020)
Education can be a measure of the progress and quality of life of a nation, so it is said that the progress of a nation and state can be achieved by one of the reforms in terms of education. In education, there are two terms, namely pedagogy and andragogy. Pedagogy is known as the education of children, while andragogy can be interpreted as the science and art of teaching adults. Children's education will take place in the form of assimilation, identification, and imitation; while adult education focuses on improving their lives, providing skills and abilities to solve problems, so what is identical here is brain training for adults. The difference between pedagogy and andragogy lies in the different assumptions about the personality of students, such as the concept of students, student experience, readiness to learn, orientation towards learning from their learning motivation. And from these assumptions, it can be distinguished in terms of the process which includes elements of atmosphere, planning, needs diagnosis, formulation, objectives, lesson plans, learning activities, and assessments.